2016
DOI: 10.1177/1056789516648370
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive inspection of initial defects of PA6.6-GF50/aluminum self-piercing riveted joints and damage monitoring under mechanical static loading

Abstract: A self-piercing riveting process is used to join a thermoplastic composite sheet of PA6.6-GF50 with an aluminum alloy sheet 5182 O. Two shapes of self-piercing rivet are tested: the countersunk rivet and the button head rivet. Non-destructive inspections by pulse thermography and post-mortem cross-section observations are made to assess the damage that might have occurred during the rivet piercing process. The manufacturing defects are characterized and the possible causes for their emergence are explained. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although this technique can indicate abnormal joints in comparison with sound joints, it is unable to tell the joint quality/features and it also cannot guarantee that the abnormal joint is a weak joint. Recently, an NDT method pulse thermography was used by Gay et al [172] to detect the defect of composite/aluminium joints. Although this method could not detect the defect of the joints, it could be used to determine the damages during lap shear tests.…”
Section: Quality Control Of Spr Jointsmentioning
confidence: 99%
“…Although this technique can indicate abnormal joints in comparison with sound joints, it is unable to tell the joint quality/features and it also cannot guarantee that the abnormal joint is a weak joint. Recently, an NDT method pulse thermography was used by Gay et al [172] to detect the defect of composite/aluminium joints. Although this method could not detect the defect of the joints, it could be used to determine the damages during lap shear tests.…”
Section: Quality Control Of Spr Jointsmentioning
confidence: 99%
“…To follow all stages of damage in steel samples subjected to a tensile test, we have used the technique of IR thermography. This technique has proven its validity in damage monitoring by using both passive and active approaches (Amiri et al., 2011; Gay et al., 2016; Vavilov and Burleigh, 2015). In our study, the test samples (width 140 mm, thicknesses 10 and 18 mm) were designed in such way that the shear bands formed close to the defects.…”
Section: Equipment and Experimental Methodologymentioning
confidence: 99%
“…With the development of technology, thermoplastic composite materials have been increasingly used in modern industry and thermoplastic joints, such as pinned joints [ 7 ], riveted joints [ 26 , 27 , 28 ], and protruding bolted joints [ 29 , 30 , 31 , 32 ], have already been focused on. Yýlmaz and Sýnmazçelik [ 7 ] carried out experimental methods to investigate the bearing performance of the pinned joints of carbon fiber/polyphenylene sulfide (CF/PPS).…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that the bearing strength of the pinned joints improved if enough end distance and width were provided. Gay et al [ 26 , 27 ] investigated the performance of a PA6.6-GF (glass fiber/polyamide)/aluminum assembly joined by self-piercing rivets under static and fatigue loads. They found that the domed head rivet achieved higher fatigue limit strength at 2 × 10 6 cycles and higher bearing strength at static loading than that of the countersunk rivet and the failure mode under the fatigue load was determined by the load amplitude and the joint geometry.…”
Section: Introductionmentioning
confidence: 99%